The O Antiphons - Dietz, Elias (Cistercian studies quarterly, 2023)
The article explores the historical significance and rich symbolism of the O Antiphons in Advent liturgy, highlighting their structure, Christological themes, and the profound catechesis on Christ, salvation, and ultimate destiny that they encapsulate. It states that each antiphon represents a prayer-like collect, invoking Christ with a Christological title, recalling aspects of salvation history, and ending with an urgent plea for His coming.